Breakfast After the Bell: The Effects of Expanding Access to School Breakfasts on the Weight and Achievement of Elementary School Children,. (April 2022) - Abouk, Rahi; Adams, Scott
Abstract: In response to lower utilization of school breakfast programs compared with school lunch programs, a number of school districts and states have mandated Breakfast After the Bell (BATB). BATB requires eligible schools to provide breakfast in the classroom each morning to all children, regardless of income. We show that there is an 11.6 percent increase in the prevalence of children who are overweight after such programs are implemented. Weights at the very low or very high end of the BMI distribution appear unaffected, however, and we find no evidence of an increase in the prevalence of obesity. Moreover, the effect is concentrated mostly on girls, low income, and black children. As for test scores, the effects tend to be positive, but not statistically significant among the early adopters of BATB programs.